Avaliação na educação infantil: percepções de professoras de um centro de educação infantil municipal de Sorocaba (SP) - Amaro, Vanélli Pires (Universidade Federal de São Carlos, 2018)
The objective of this research was to investigate how the teachers of a municipal education center in Sorocaba (SP) perceive the process of evaluation of children in pedagogical practice. The interest in the research theme came up in a context of changing the guidelines of the Municipal Department of Education in relation to the process of evaluation of children in early childhood education, through the document Guidelines for Pedagogical Documentation in Early Childhood Education. This qualitative research (LUDKE and ANDRÉ, 1986) used the methodology of case study, according to Yin (2001), seeking to apprehend the teachers' conceptions about the evaluation process, through interviews and consultation of documents. Understanding evaluation as an inseparable part of pedagogical practice, from a mediating perspective (HOFFMANN, 2014) whose objective is to make decisions to favor student learning (LUCKESI, 2002), without anticipating fundamental education practices (GODOI, 2010; MORO, 2016), we tried to answer the following questions: What conceptions do the teachers present about the evaluation process in early childhood education? How are their evaluation practices and what pedagogical guidelines do they seek to follow in order to achieve them? Which relationships do teachers establish between evaluation and the teaching-learning process of children? With the presentation of the document of the Municipal Education Department there was a proposal for a change of assessment instruments. However, in addition to the evaluation instruments, the document also presented the conception of children as a historical and rights subject (BRASIL, 2009a), being a participant as person and as a citizen in the various social contexts, as well as in the construction of knowledge and culture (OLIVEIRA-FORMOSINHO, 2007). Through the analysis of data it was possible to identify that, although they understand some aspects of the evaluation in a different way, the teachers conceive that their completion occurs daily and using various forms of registration, according to the guidelines of the document and the design of pedagogical documentation. Were verified progress and difficulties faced by teachers in this process of new conceptions and evaluation practices, as well as relationships established with their pedagogical practices. The research poses as a possibility to broaden the discussions on evaluation in early childhood education, in the search for progress in the aspects that are still necessary, so that it approaches more and more of offer of a quality education for young children.
Evaluation in early childhood education: teachers' perceptions of a municipal child education center in Sorocaba (SP)
Keywords: Avaliação; Educação Infantil; Documentação Pedagógica; Evaluation; Early Childhood Education; Pedagogical Documentation; Professores de educação infantil; Professores de educação infantil; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL